Household Energy for Cooking : Project Design Principles - Ekouevi, Koffi (World Bank Group, Washington, DC, 2015)
Reliance on solid fuels for cooking is an indicator of energy poverty. Access to modern energy services - including electricity and clean fuels - is important for achieving the Millennium Development Goals. It can also reduce womens domestic burden of collecting fuelwood and allow them to pursue educational, economic, and other employment opportunities that can empower them and lead to increased gender equality. Similarly, the use of clean cooking and heating fuels in efficient appliances can reduce child mortality rates. Without access to modern energy services, the likelihood of escaping poverty is very low. Interventions to improve energy access to the poor have focused mainly on electricity access and have often neglected nonelectricity household energy access. Household energy for cooking in particular has received little policy attention in the overall energy sector dialogue, and consequently its lending volume remains low, in spite of the magnitude of the development challenges it represents. The objective of this note is to assist task teams with broad project design principles related to household energy for cooking. It follows five main reports produced by the World Bank Group over the last three years: (1) Household Cookstoves, Environment, Health, and Climate Change: A New Look at an Old Problem; (2) Household Energy Access for Cooking and Heating: Lessons Learned and the Way Forward; (3) One Goal, Two Paths Achieving Universal Access to Modern Energy in East Asia and Pacific; (4) Wood-Based Biomass Energy Development for Sub-Saharan Africa; and (5) What Have We Learned about Household Biomass Cooking in Central America? These reports make the case for a re-engagement of the World Bank Group in the household energy access sector. This note is organized into two sections: (a) context and background, and (b) project design principles.